Vendor qualification: Utilization of solid state characterization “Toolbox” to assess material variability for active pharmaceutical ingredient - Devarajan Saravanan, Prakash Muthudoss, Praveen Khullar, Ambrose Rosevenis (Journal of Applied Pharmaceutical Science, 2019)
One of the credos for a successful product development, early clinical trial supplies, achieving full-scale manufacturability and speed to the market is the vendor qualification. The focus of this paper is to employ a systematic approach to qualify different active pharmaceutical ingredient (API) suppliers. In this context, API sourced from two different vendors used in product development, where prototype formulations manufactured with identical components and specifications demonstrated significant variations in drug product performance attributable to vendor-to-vendor variability. Prototype prepared using API (Vendor 1) showed disintegration of tablets in 4.5 minutes which complied with in-house specifications, whereas it was >15 minutes for the prototype prepared from API (Vendor 2). In order to understand these differences, a vast array of solid state techniques were employed to compare the critical material attributes of API (GDCS1902) from two different Vendors. Furthermore, these tools were orthogonally applied to understand whether API from two Vendors demonstrated any process-induced transformations, such as process-induced polymorphism, process-induced crystal disorder, and process-induced fragmentation. The results of these measurements indicated the presence of fine particles of varied morphology with API (Vendor 1), while API (Vendor 2) showed more medium-sized uniform particles. Formulation process modification to induce API fragmentation in situ was carried out for the API from Vendor 2. This modification produced desired granule properties which were then subjected to drug performance tests and was found to match the specification. This study demonstrates the importance of understanding the critical material attributes to match the final product performance when multiple vendors were selected.
Keywords: Vendor qualification, drug product performance testing, solid state characterization techniques, in situ process-induced fragmentation, critical material attributes.